Peripheral Citizens: “colonial Christians,” Caste, and the Politics of Minoritization in Postcolonial Literature - (:unkn) unknown (My University, 2023)
My dissertation looks at the politics of minoritization of Christian communities in post-independent India. I use the term “colonial Christians” as a descriptive category to analyze the three Christian groups (Anglo-Indians or Eurasians, poor domiciled Europeans employed by the Raj, and lower-caste Christian converts) that were formed in the colonial period either by inter-racial mixing between the British and South-Asians or due to Christian missionary conversion. The communities are not united simply by the virtue of their faith. The internalized hierarchy based on class, gender, caste, skin color, European lineage, and access to the English language creates a crucial axis of minoritization for the underprivileged members of the group. Colonial policies and their legacies in the post-colonial nations, the internalized racism, classism, and sexism that defined colonial bureaucracy, and later, absorbed into the scaffolds of the Catholic and Protestant Churches in India provide a postcolonial lens to analyze the multiple processes of marginalization of colonial Christians in post-independent India. Overall, the dissertation is interested in exploring the duality of this group, being Indian and Christian, and how this hyphenation is played out in post-colonial literature published after India’s independence in 1947. The politics of minoritization serves as a theoretical framework to analyze how members of colonial Christian groups evaluate multiple histories and various determinants to contextualize their own marginalization. The contested relationship among Christian characters, the awareness of ambiguous colonial policies, and the resultant internal hierarchization based on race, ethnic origin, class, and skin color are explored in the postcolonial texts to show the various axes of minoritization of the fictional characters. This dissertation will look at different genres of literature: short stories, memoirs, post-1947 Raj novels, and Dalit writings to complicate the understanding of minoritization by exploring questions on citizenship, national belonging, dislocation, and marginalization that this heterogeneous minority group faces in independent India. To explore the complex orchestration of minority politics in postcolonial fiction, the dissertation will look at only three Christian groups (not the whole community) that have a complicated entry into the project of nation-building after India’s independence. Though there is rich scholarship on each of the three Christian groups focusing mostly on hybridity and marginalization, I believe the interconnectedness, as well as the tensions and contradictions among and between the groups, have not received enough attention, particularly in the discipline of literary criticism. This dissertation addresses the gap in scholarship to interrogate the narrative space of postcolonial fiction.
Keywords: Christian minority groups in India; colonization; politics of minoritization; postcolonial literature